A prospective observational study of morbidity and mortality profile of neonates admitted to neonatal intensive care unit in a tribal area of central India (Indian Journal of Child Health, 2018)
Introduction: Globally, 2.6 (2.5–2.8) million newborns died in 2016 or 7000 every day. High neonatal mortality rate reflects the presence of unfavorable social, economic, and environmental conditions. Objectives: To find morbidities and causes of poor outcome in a tertiary care neonatal unit of eastern part of Maharashtra. Materials and Methods: The present prospective observational study was conducted in the neonatal intensive care unit of a tertiary care center, Gondia, in Central India which is situated in remote, tribal place during. Data were collected by interview method using a predesigned, semi-structured questionnaire. Neonatal variables used were total number of admissions, gender, birth weight, and gestational age, diagnosis at admission, final outcome, and duration of stay. Results: There were a total of 2017 admissions during the study period and out of them, 62.96% were inborn neonates and 37.04% were outborn. Males (56.67%) had slightly higher admission rate than females (43.33%). Pre-term admissions were 40.06%. The majority of admissions were due to low birth weight (LBW) (60.19%). Preterm and related complications (49.43%) were ranked highest followed by jaundice (16.46%). Out of the total 2017 neonates, 218 died following admission. Prematurity (45.41%) followed by sepsis (22.48%) were reasons for mortality among neonates. Conclusion: We have tried to present neonatal morbidity pattern and outcome parameters from a tertiary care neonatal center in a developing country. Prematurity, sepsis, and birth asphyxia were accounting for morbidities and mortalities. The preterm and LBW babies had significantly higher mortality even with standard intensive care.